2014
DOI: 10.5489/cuaj.2415
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of genetic testing for hereditary kidney cancer in Canada is lacking: The results of the Canadian national hereditary kidney cancer needs assessment survey

Abstract: Introduction: Treatment of hereditary renal cell carcinoma (HRCC) requires a multidisciplinary approach that may involve medical oncologists, geneticists, genetic counsellors, and urologists. The objective of our survey was to obtain current and representative information about the use and perceived importance of genetic testing for HRCC in Canada. Methods: A self-administered web-based survey was provided to Canadian medical oncologists, geneticists, genetic counsellors, and urologists in collaboration with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Another possibility is a lack of knowledge or access to genetic testing facilities. Barriers to genetic testing for patients with kidney cancer in Canada were assessed by Violette et al [13]. The main barriers were identified as lack of provider knowledge about availability and clinical impact of genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is a lack of knowledge or access to genetic testing facilities. Barriers to genetic testing for patients with kidney cancer in Canada were assessed by Violette et al [13]. The main barriers were identified as lack of provider knowledge about availability and clinical impact of genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Training in genetic research and genetic counselling needs to be expanded into undergraduate medical and other health professions training programs, to further expand expertise, especially in under-resourced communities. The diversification of training is important especially in under-resourced communities, as the liberty to have standalone genetic counsellors is not a luxury all can afford ( 32 , 33 ) The format of training in South Africa for those who do genetic counselling in psychiatry and schizophrenia, more specifically would also need to be made fit-for-purpose in specific regions. The qualification in South Africa and other African countries has great potential and opportunities for development because it is a relatively young field of specialization—especially in the context of accreditation of fit-for-purpose courses and qualifications.…”
Section: Recommendations and Opportunities For Improving Genetic Coun...mentioning
confidence: 99%
“…Norms need to be developed to address the translation of basic concepts on genetic information into indigenous languages. The maintenance of good quality translation for diverse populations and end-users could be extended beyond a condition such as schizophrenia and psychiatry but could encompass other disciplines within which training and accreditation bodies like the Health Professions Council of South Africa (HPCSA) and similar bodies across the global South and the North, could expand ( 32 ). Such norms can be a basis for guidelines for the setting of minimal information and concepts that need to be covered in patient information and participant information leaflets in the context of genetic counselling or genetic research.…”
Section: Recommendations and Opportunities For Improving Genetic Coun...mentioning
confidence: 99%
“…A Surveillance, Epidemiology, and End Results Program (SEER) database study identified all patients with a known kidney cancer diagnosis, and found that 24% of patients met ACMG/NSGC genetic referral criteria based on RCC histologic subtypes alone, suggesting that patients are under-referred for genetic counseling 12 . Provider knowledge, accessibility to a genetics unit, possible lack of clinical impact and wait times have been identified as barriers to genetic testing referrals for patients with suspected hereditary RCC amongst Canadian urologists 13 . From a patient perspective, it has been shown that cost of testing in women with breast cancer is an established barrier for undergoing genetic assessment, and therefore patients often decline referral to a geneticist 14 .…”
Section: Cuaj -Original Researchmentioning
confidence: 99%